Tuvan folk medicine through doctors’ eyes: a survey of physicians and other medical personnel in the Republic of Tuva and its environs - Vyatkina, Natalia A. (The New Research of Tuva, 2018)
In the Republic of Tuva, people increasingly often appeal to various forms of traditional medical and preventive practices. In some cases, these practices even compete with Western medicine (biomedicine). The article is devoted to the study of the influence various traditional medical, preventive and shamanic practices, widespread in Tuva, have on the relationship between the doctor and the patient. Our study is based on the outcomes of a survey of 22 physicians of different medical specializations in the Republic of Tuva, as well as in the neighboring regions — the Republic of Khakassia, Altai and Krasnoyarsk regions – made in 2018. The opinions we have collected relate to various forms of traditional medical practices and folk healing common in the regions of Russia with considerable ethnic and cultural minority presence. Physicians agreed to participate in the survey upon condition of strict anonymity and used a variety of terms to refer to traditional medical and preventive practices or folk healing. All respondents hold that alternative methods of treatment are unjustified, while medical advice is seen as the only key priority in healthcare. All of them believe in "real" medicine. When asked to name the main reasons why patients go to healers, physicians named the lack of treatment effect in hospitals, poor quality of medical services provided there, territorial inaccessibility, high cost of paid services, cultural characteristics, family traditions and education in Tuva and nearby regions, etc. The general attitude of physicians to healers is skeptical, although some methods, such as herbal medicine, are not rejected outright. They also accept the use of such methods for themselves and their families, either at home or in specialized clinics. Widely different are the opinions of another group of physicians in Tuva – those who accept the special role of cultural traditions in healing, among other areas of human experience.